Impact study the costs necessary to conserve biodiversity on the farm Agrozootehnica Roseti - Anisoara Chihaia; Georgiana Melania Costaiche; Octavian Chihaia (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 3rd Edition of the International Symposium, October 2012, Bucharest, 2012)
Biodiversity embraces the variety of genes, species and ecosystems that constitute life on Earth. We are currently witnessing a steady loss of biodiversity, with profound consequences for the natural world and for human well-being. Appears necessary to increase the positive contribution of agriculture to the environment, the need to reduce pollution from agriculture and adoption of agricultural policy so that it takes account of the environment. Standards or requirements that farmers must meet to be eligible for subsidies contribute to maintain biodiversity. The purpose of this paper is to estimate the costs needed to implement environmental standards and their implications for farm profitability. This study was made in a farm in the south part of Romania. Compliance with these rules increases variable costs. Therefore, an appropriate method for measuring the profitability of farm production activities would be gross margin calculated for each type of farm activity. Even if it can be seen a increase of production expenses which lead to a light decrease of farms profitability, the long-term benefit of biodiversity conservation is considerably.
Keywords: 330; biodiversity; costs; gross margin; profitability; standards or requirements